The impact of Chinese companies' cross-border mergers and acquisitions on the stock market and shareholders - Xin, Lian (2020)
For the developing of companies, cross-border mergers and acquisitions have increasingly begun to be a main way for companies to go to the world and obtain more resources and benefits. Cross-border mergers and acquisitions also act a pivotal part in in the development of the world economy. Therefore, both developed and emerging economic markets are very concerned about transboundary mergers and acquisitions.